Propuesta de comunicación para la Escuela de Administración de Empresas del Tecnológico de Costa Rica basado en INSIGHTS de mercado - Cisneros-Hernández, Gabriel; Monge-Elizondo, Ileana; Rodríguez-Valerio, César; Segura-Chavarria, Sheiris; Vargas-Salazar, Gisela (Instituto Tecnológico de Costa Rica, 2015)
At a university level, competition has increased due to the opening of a large number of private universities throughout Costa Rica in recent years. Beside the prestige and quality that represents a public university; all of them have been affected by this oversupply of university careers. Being affected by this phenomenon, the Tecnologico de Costa Rica requires marketing actions to help to decrease the impact of the competition. This dilemma is not only affecting the institutional level, it also creates problems at the Escuela de Administracion de Empresas (Business Administration school). Neither the Tecnologico de Costa Rica nor the Escuela de Administracion de Empresas have conducted investigations at “insights” level. This methodology is not widely used by the institution for marketing purposes. This research is the first that manages to penetrate the mind of the prospective and current student in order to have find things that no one expected about the beliefs of these populations. The research results allow going further in marketing terms to make future communication campaigns both internal and external. Using a qualitative methodology with tools like “focus groups” was how we entered in the student's mind. The “insights” found by this research are the results of the thoughts of fifth grade students, freshmen college and third year university students of the business administration career. This results can be used both by the Tecnologico de Costa Rica and the Escuela de Administracion de Empresas for future communication or advertising campaigns.
Proyecto de Graduación (Licenciatura en Administración de Empresas. Énfasis en Mercadeo) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2015.
Keywords: Marketing; Comunicación; Estudio de mercados; Mercadeo